2021
DOI: 10.3390/vaccines9070694
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Transcriptome and Gut Microbiome on the Response of HIV-1 Infected Individuals to a Dendritic Cell-Based HIV Therapeutic Vaccine

Abstract: Therapeutic vaccines based on dendritic cells offer a good approach to HIV-specific T-cell responses and partial control of the viral load after antiretroviral therapy interruption. The aim of the present study was to identify mRNA expression profiles and to assess the impact of the gut microbiome composition for predicting the viral load control after antiretroviral therapy interruption. We enrolled 29 patients to receive either placebo or a monocyte-derived dendritic cell vaccine. Patients with a decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Also, elite controllers, who spontaneously control HIV replication without ART, showed higher gut microbial richness with a metabolic profile resembling that of HIV-uninfected adults [ 50 ] and increased Th17 cells in the gut mucosa compared to ART-treated patients [ 51 ]. In line with our results, a recent study showed enriched levels of Bacteroidetes genera, such as Bacteroides and Prevotella , in patients with sustained HIV control during ART interruption, after receiving dendritic cells-based HIV-1 immunization [ 52 ]. Moreover, additional evidence on HIV virologic controllers receiving a TLR7 agonist before ART interruption with baseline enrichment in P. copri and negative association between abundance of Ruminococcus gnavus and time to viral rebound suggested a potential impact of certain microbiome species on HIV persistence [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
“…Also, elite controllers, who spontaneously control HIV replication without ART, showed higher gut microbial richness with a metabolic profile resembling that of HIV-uninfected adults [ 50 ] and increased Th17 cells in the gut mucosa compared to ART-treated patients [ 51 ]. In line with our results, a recent study showed enriched levels of Bacteroidetes genera, such as Bacteroides and Prevotella , in patients with sustained HIV control during ART interruption, after receiving dendritic cells-based HIV-1 immunization [ 52 ]. Moreover, additional evidence on HIV virologic controllers receiving a TLR7 agonist before ART interruption with baseline enrichment in P. copri and negative association between abundance of Ruminococcus gnavus and time to viral rebound suggested a potential impact of certain microbiome species on HIV persistence [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
“…These studies have reported inconsistent results. In humans, the administration of oral typhoid or an intranodal and intramuscularly human immunodeficiency virus (HIV)-1 vaccine was not reported to significantly affect the composition of the intestinal microbiota one week to several months after vaccination 12 , 21 , 22 . The first two studies used amplicon sequencing, while the third used shotgun metagenomic sequencing.…”
mentioning
confidence: 99%
“…The effect of vaccine administration on the intestinal microbiota has gathered even less attention. Previous works investigating the effects of HIV-1 14,15 and oral typhoid 16 vaccines on the human gut microbiota reported no discernible perturbations of the microbial community structure induced by vaccination. In contrast, an increase in the Firmicutes/Bacteroidetes ratio following HIV-1 DNA/ protein immunization was observed in the rectal microbiome of non-human primates 17 .…”
Section: Introductionmentioning
confidence: 79%